Use of a child’s image for advertising on social networks - Jasinskaitė, Beatričė; Ubavičiūtė, Monika (Vilnius University Open Series, 2021)
The research is mainly focused on taking legal regulatory measures that ensure the child’s rights to share information on the internet space, because the child is a vulnerable member of society. The current regulatory mechanism is not capable of protecting the rights of a child when his or her image is appropriate for promotional social networks. For this reason, the child may experience parental abuse of power, the child’s right to rest is not guaranteed, as well as the principle of separation of property.